Managing intellectual capital in organizations operating in Singapore : an exploratory research. - See, Eunice Shumei. (2008)
This report provides insights of the Intellectual Capital Management (ICM)processes in organizations operating in Singapore and highlights the significance of ICM in these organizations. This research has adopted a case study approach, involving interviews with organizations from various industries operating in Singapore.